The Impediment for Public Procurement with the Linked Legal Entity - Armas Diéguez, Silvana Lorena (2015)
This paper analyzes from a constitutional perspective, applying the test of proportionality about limiting rights, the impediment to hiring those associated corporations, through individuals, with those legal persons which has imposed a sanction temporary or permanent disqualification from government contracts. From this framework of study, the author finds that the interference on freedom of contract is disproportionate because it violates the principle of causality and strict liability, by attributing to a third party (legal person linked) consequences for the actions made to it by a different legal entity.